Invisible from view: leaving and aftercare provision in the Republic of Ireland - Carr, Nicola (Taylor & Francis, 2014)
The adequacy of provisions for young people leaving care and in aftercare in the Republic of Ireland have been the subject of recent policy attention. A landmark report, the Ryan Report (2009), into historic abuse in state institutions recommended strengthening provisions in this area. However, the legislative basis for aftercare remains relatively weak and services for young people leaving care remain ad hoc and regionally variable. This article outlines the current context of leaving and aftercare provision in the Republic of Ireland and traces some of the recent policy debates and recommendations in this area. A genealogical analysis of leaving care and aftercare provision highlights that this issue has historically only emerged as a concern in the context in which young people leaving the care system are perceived as a ‘threat’ to social order. It is argued that the failure to adequately reform leaving and aftercare provision is reflective of wider social inequality and of a context in which young people in care are largely invisible from view.